'What should a woman do and imagine to have bulimia?': Co-constructing patient expertise in psychotherapy with bulimia patients. (29th May 2017) - Pawelczyk, Joanna; Talarczyk, Małgorzata
Abstract : One of the goals of psychotherapy with bulimia patients is identification of the functions of the eating disorder in their lives. Thus, as in any psychotherapeutic approach, the therapist should facilitate the patient's disclosure of his or her experience of living with bulimia. Talking about one's dysphoric experiences and, particularly in the case of bulimia, symptoms and experiences that commonly deprive people with bulimia of dignity, constitutes an emotional challenge for the patient and an equally challenging interactional task for the therapist. Using the example of one therapy session with a female bulimia patient, we examine how the therapist and the patient interactionally engage in co-constructing the patient's expertise – involving epistemics of experience as well as epistemics of expertise – concerning the illness in the interactional here-and-now. Applying tools and insights from discourse and conversation analysis, we examine the sequences in which the patient shifts the topical focus from a general observation concerning bulimia to her personal experience, to be further pursued interactionally by the therapist. We also discuss how the therapist downgrades her epistemic position and (concurrently) foregrounds and bolsters the patient's voice as expert to accomplish the session's therapeutic goals.